Africa's Economic Growth: Opportunities and Constraints. - Collier, P (2007)
Africa's economies have diverged from other developing regions: over the past three decades growth has been much slower. In this paper I relate this to the region's distinctive physical and political geography. These features not only make Africa different from other regions, they make some parts of Africa radically different from others. Understanding these differences is critical because they imply equally substantial differences in opportunities and hence in the strategies likely to be effective for growth. No pan-African growth strategy offers a realistic prospect of success, nor can Africa simply copy the strategies of successful regions that have fundamentally different physical or political geography. I propose three strategies each of which is likely to be appropriate for a part of the region.